2017
DOI: 10.5815/ijmecs.2017.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic Evaluation of the use of Blackboard & Facebook Groups in Computing Higher Education

Abstract: Abstract-The features of social media sites make them potentially effective as a learning platform for student communication and collaboration in higher education. Moreover it has become apparent that student Facebook users have been repurposing its features to fit their academic requirements. This study aims to determine if Facebook Groups and the Blackboard Learning Management System (LMS) can enhance the learner experience, and if so, in what way. The study made use of a heuristic evaluation with an educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…For example, Facebook is a social network that is used for educational purposes as an educational tool [15]- [17]. In their study [18] confirmed former results in the literature in regard to the usefulness of Facebook (a Social networking site) for learning; that Facebook provides key approaches for learning and it is useful for effective communication between peers. Moreover, C. Lampe et al [19] investigated how do students perceive using Facebook for classroom-related collaborative activities and found that using social media tools improved students' self-efficacy and create students who are motivated to communicate with others.…”
Section: The Use Of Social Network Sites (Snss) Cloud Storages Services and File-sharing Services In Educationsupporting
confidence: 66%
“…For example, Facebook is a social network that is used for educational purposes as an educational tool [15]- [17]. In their study [18] confirmed former results in the literature in regard to the usefulness of Facebook (a Social networking site) for learning; that Facebook provides key approaches for learning and it is useful for effective communication between peers. Moreover, C. Lampe et al [19] investigated how do students perceive using Facebook for classroom-related collaborative activities and found that using social media tools improved students' self-efficacy and create students who are motivated to communicate with others.…”
Section: The Use Of Social Network Sites (Snss) Cloud Storages Services and File-sharing Services In Educationsupporting
confidence: 66%
“…Combining the breakout groups with the discussion board posts, again allows not just for interaction, but a more enriched and interactive learning experience. There is ample literature that supports that peer-to-peer instruction is very effective ( Carmichael & MacEachen, 2017 ; Katsifli et al., 2010 ;). It has been our consistent experience that students will present explanations or provide illustrations of concepts that facilitate the learning process of their peers.…”
Section: Suggestions For Developing Online Etiquette and Professional Behavioursmentioning
confidence: 99%
“…Heuristic evaluations have been used to improve e-learning and online instruction, such as web-based writing courses (Miller-Cochran & Rodrigo, 2006), web-based tools for collaboration (Hvannberg et al, 2007), web-based support for competence maps (Stoof et al, 2007), online employee training (Zaharias & Poulymenakou, 2009), MOOC-like online courses (Zaharias & Koutsabasis, 2012), virtual laboratories (Davids et al, 2013), game-based social skills training (Tan et al, 2013), and peer communication (Carmichael & MacEachen, 2017). These tests were able to reveal issues in system design (e.g., access, navigation, and clarity), which allowed the developers to address problems in future studies or interventions.…”
Section: Heuristic Evaluations Of Srl Designmentioning
confidence: 99%